The timecourse of space- and object-based attentional prioritization with varying degrees of certainty - Drummond, Leslie; Shomstein, Sarah (Frontiers in Integrative Neuroscience, 2013)
The relative contributions of surfaces (i.e., object-based) and underlying spatial representations (i.e., space-based) to attentional prioritization and selection remain unclear. In most experimental circumstances, the two representations overlap thus their respective contributions cannot be evaluated. Here, a dynamic version of the two-rectangle paradigm allowed for a successful de-coupling of spatial and object representations. Space-based (cued spatial location), cued surface (cued location on an object), and object-based (locations within the cued object) effects were sampled at several timepoints following the cue with high or low certainty as to target location. In the high uncertainty condition spatial benefits prevailed throughout most of the timecourse, as evidenced by facilitatory and inhibitory effects. Additionally, the cued surface, rather than a whole object, received the attentional benefit. When target location was predictable (low uncertainty manipulation), only probabilities guided selection (i.e., biased location received the benefit). These results suggest that with high uncertainty as to the location of the upcoming target, all available information present within the stimulus display is used for the purposes of attentional selection (e.g., spatial locations, surfaces) albeit to varying degrees and at different time points. However, as certainty increases, only spatial certainty guides selection (i.e., surfaces and objects are filtered out). Taken together, these results further elucidate the contributing role of space- and object-representations to attentional guidance.